Boron deficiency‐induced root growth inhibition is mediated by brassinosteroid signalling regulation in Arabidopsis. (5th July 2021) - Zhang, Cheng; He, Mingliang; Wang, Sheliang; Chu, Liuyang; Wang, Chuang; Yang, Ningmei; Ding, Guangda; Cai, Hongmei; Shi, Lei; Xu, Fangsen
Summary: Brassinosteroids (BRs) are pivotal phytohormones involved in the control of root development. Boron (B) is an essential micronutrient for plants, and root growth is rapidly inhibited under B deficiency conditions. However, the mechanisms underlying this inhibition are still unclear. Here, we identified BR‐related processes underlying B deficiency at the physiological, genetic, molecular/cell biological and transcriptomic levels and found strong evidence that B deficiency can affect BR biosynthesis and signalling, thereby altering root growth. RNA sequencing analysis revealed strong co‐regulation between BR‐regulated genes and B deficiency‐responsive genes. We found that the BR receptor mutants bri1‐119 and bri1‐301 were more insensitive to decreased B supply, and the gain‐of‐function mutants bes1‐D and pBZR1‐bzr1‐D exhibited insensitivity to low‐B stress. Under B deficiency conditions, exogenous 24‐epibrassinolide rescued the inhibition of root growth, and application of the BR biosynthesis inhibitor brassinazole exacerbated this inhibitory effect. The nuclear‐localised signal of BES1 was reduced under low‐B conditions compared with B sufficiency conditions. We further found that B deficiency hindered the accumulation of brassinolide to downregulate BR signalling and modulate root elongation, which may occur through a reduction in BR6ox1 and BR6ox2 mRNA levels. Taken together, our results reveal a role of BR signalling in root elongation under B deficiency. Significance Statement: Boron deficiency severely inhibits the growth of primary roots, but the regulatory mechanisms are still poorly understood. Our findings suggest that B deficiency reduces the accumulation of brassinolide by reducing BR6ox1 and BR6ox2 mRNA levels to downregulate brassinosteroid signalling and modulate root elongation.